(untitled) (Advances in Applied Biological Research, 2026)
Human metapneumovirus (HMPV) is one of the primary sources of severe respiratory infections worldwide. The threat level of the virus is almost the same as that of influenza and RSV, and it is mostly difficult for the vulnerable trio of neonates, the elderly, and immunocompromised patients to deal with. Although it took approximately four decades from the time it had been circulating before it was identified in 2001, it still has no vaccine or antiviral drugs. The current review sheds light on HMPV’s genetic lineages and worldwide transmission, emphasizing how bioinformatics has changed its research. Advanced sequencing enables detailed phylogenetic tracking of the virus, whereas computational tools, such as AlphaFold2, help obtain an accurate protein structure. Such breakthroughs can attract the development of drugs through molecular docking and epitope generation for vaccine design. The molecular dynamics simulations also show the viral fusion protein conformational transitions, among other key processes, On the road to success there are still some major gaps in knowledge, such as host receptor identification Integrating these computational approaches is essential to accelerate the development of therapies and reduce the global HMPV burden.